Answer:
The value of x is equal to -2/3.
Step-by-step explanation:
In the problem it says that y equals 2x, and that 3x - 3y = 2.
The first step is to substitute 2x into y.
3x - 3(2x) = 2.
The next step is to use distributive property.
-3(2x) = -6x.
Now we need to add like terms.
3x - 6x = -3x.
Which gives us the equation -3x = 2.
The final step is to divide on both sides to get the value of x.
-3x/-3 = 2/-3.
x = -2/3.
So as you can see, x is equal to -2/3.
We can also check to make sure by redoing the problem, but substituting the value of x.
3(-2/3) - 3(2 * -2/3) = 2.
-2 - 3 * -4/3 = 2.
-2 + 4 = 2.
2 = 2.
The value of x is indeed -2/3.
Answer:
See below for explanation of the examples.
Step-by-step explanation:
Left example
It is an exercise in addition, i.e. 48+122=170, the answer is written in the bottom box.
Right example
It is an exercise in subtraction, i.e. 8 1/2 - 3 1/2 = 5
The answer is written in the bottom box.
There is no indication though as to when to do the addition, and when to do the subtraction. Perhaps it would be shown in the rest of the page (not shown).
Answer: 3x^4 +x^3 -2x^2 +3x +2
Step-by-step explanation:
(3x^4 - 2x^3 + 4x -2) + (3x^3 - 2x^2 - x +4)
There are no like terms for 3x^4, so leave it alone.
-2x^3 + 3x^3 = 1x^3
No like terms for -2x^2
4x - x = 3x
-2 + 4 = 2
Answer? 3x^4 +x^3 -2x^2 +3x +2
(Please mark brainliest! :) )